ASUHAN KEPERAWATAN PADA ANAK S DENGANASMA BRONKHIAL DI LINGKUNGAN RT 01 RW 07 KELURAHAN LIMO KECAMATAN LIMO DEPOK - Ulya Shafa Luthfiah, (2023)
Bronchial asthma is a serious respiratory disease that often occurs in children, which not only interferes with daily activities, but can also affect children's growth and development. Children will feel disturbed in activities such as eating, drinking, playing, studying, school, sleeping and other activities. When a bronchial asthma attack occurs, the child will feel short of breath, the frequency of breathing is fast, they get tired easily, it is difficult to breathe. Asthma will cause coughing and even accompanied by excess phlegm which causes obstruction of the supply of oxygen to the respiratory tract so that it will cause a sound when breathing which is called wheezing. Methods: This research was conducted using a case study method of nursing care in Child S with bronchial asthma in the RT area. 01 Rw. 07 Kelurahan Limo Limo District on 23-25 February 2023. Data collection was through interviews, observation, physical examination and documentation. Results: The main nursing diagnosis of ineffective airway clearance is related to airway spasm characterized by excess sputum. Nursing interventions carried out were monitoring breathing patterns, monitoring additional breath sounds, semi-Fowler's position, giving warm drinks, teaching effective coughing techniques, collaborating with bronchodilators. Implementation of nursing in accordance with nursing interventions that have been made and evaluate nursing. Within 3x24 hours the problem of acute pain can be resolved. Conclusion: The care that has been given to Child S based on nursing care can be partially resolved, Childs no longer congested, but still coughing up phlegm, Child S can cough effectively, crackles have decreased, and sputum has decreased.